Genetic and evolutionary computing proceeding of the Eight International Conference on Genetic and Evolutionary Computing, October, 18-20, 2014, Nanchang, China - International Conference on Genetic and Evolutionary Computing Nanchang, China) 2014; Sun, Hui; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This volume of Advances in Intelligent Systems and Computing contains accepted papers presented at ICGEC 2014, the 8th International Conference on Genetic and Evolutionary Computing. The conference this year was technically co-sponsored by Nanchang Institute of Technology in China, Kaohsiung University of Applied Science in Taiwan, and VSB-Technical University of Ostrava. ICGEC 2014 is held from 18-20 October 2014 in Nanchang, China. Nanchang is one of is the capital of Jiangxi Province in southeastern China, located in the north-central portion of the province. As it is bounded on the west by the Jiuling Mountains, and on the east by Poyang Lake, it is famous for its scenery, rich history and cultural sites. Because of its central location relative to the Yangtze and Pearl River Delta regions, it is a major railroad hub in Southern China. The conference is intended as an international forum for the researchers and professionals in all areas of genetic and evolutionary computing.
Nature Inspired Constrained Optimization -- Recent Advances on Evolutionary Optimization Technologies -- Wearable Computing and Intelligent Data Hiding -- Image Processing and Intelligent Applications -- Intelligent Multimedia Tools and Applications -- Technologies for Next-Generation Network Environments.
Electronic reproduction.
Keywords: Genetic programming (Computer science) -- Congresses; Genetic algorithms -- Congresses; Evolutionary computation -- Congresses; Electronic books